Designing women's snowboarding clothing: application and expansion of the FEA consumer needs model - Emerich, Paige, author; Sanders, Eulanda, advisor; Yan, Ruoh-Nan, committee member; Campbell, Sue Ellen, committee member (Colorado State University. Libraries, 2011)
This mixed-methods research study examined women's snowboarding clothing preferences in relation to Lamb and Kallal's (1992) FEA Consumer Needs Model. A fourth element, environmental, was proposed as an addition to the model but its inclusion was not supported. The model was used to guide the study and garment design. Fifteen women snowboarders participated in an interview and survey about their snowboarding clothing desires and preferences. The data from the initial interview and survey was used to create two prototype snowboarding jackets and two prototype snowboarding pants. Photos and fabric swatches of the garments were analyzed by the original participants to complete the prototype evaluation survey feedback. Fourteen participants participated in the prototype evaluation survey. Results showed the participants rated functional garment elements as the most important consideration followed by the aesthetic elements, expressive elements, and finally environmental elements. Although color was an extremely important garment element, prototype evaluations showed the participants preferred the monotone black, feminine fitted jacket and the gray pinstripe, sleek fitting pant. Participants were not willing to spend more than 50 dollars more than their original budget nor would they give up any functional features because of the garment's environmental properties.
Keywords: athletic apparel; women's apparel; snowboard clothing; environmentally friendly apparel